Multifractal modeling of MPEG-4 video traffic - WANG Sheng-hui; QIU Zheng-ding (Tongxin xuebao)
The correlation function and marginal distribution of multipliers at each layer were investigated in multifractal multiplicative process.Based on the lemmas gained,a new multifractal MPEG-4 video traffic model（PMFM,predict-able MFM）was proposed.By modeling the coarsest coefficients with the auto-regressive（AR） process,PMFM has the ability of traffic prediction that traditional MFM do not have.Furthermore,the model stability and robustness were also improved by changing the way of parameter estimation.